Factors Affecting Consumer Purchase Decision of Laptops - Soni, Ravi; Lohani, Rohit; Sagar, Mahim (Indian Journal of Marketing, 2010)
A comparative study of the various sales pamphlets of different laptop producing companies seems to suggest that almost all the laptop brands offer nearly the same configuration (processors, RAM and graphics cards) and features (webcams, fingerprint scanners) in their products to the consumers. None of the brands can be seen as enjoying their product as exceedingly superior to its competition. With all things virtually equal within the box, what is it that makes a consumer choose one brand over another (Brand Preference and Product Differentiation)? Is it still within the box or outside of it that drives the decision? What is it that compels a consumer to purchase the Dell laptop instead of the HP when a consumer is comparing them side by side? Is it just the price? Did the consumer previously had a bad experience with HP? Are the Dell commercials intriguing enough to make consumers buy their products? Does a younger family member, with a higher degree of technical competency, tell an older family member that Dell is the only thing to buy? While the evaluative buying criteria consumers use when purchasing these products maybe known, what was not known was the impact each of them have in contributing to that decision.